2015
DOI: 10.1016/j.jacc.2015.02.043
|View full text |Cite
|
Sign up to set email alerts
|

2015 SCAI/ACC/HFSA/STS Clinical Expert Consensus Statement on the Use of Percutaneous Mechanical Circulatory Support Devices in Cardiovascular Care

Abstract: Although historically the intra-aortic balloon pump has been the only mechanical circulatory support device available to clinicians, a number of new devices have become commercially available and have entered clinical practice. These include axial flow pumps, such as Impella V R ; left atrial to femoral artery bypass pumps, specifically the TandemHeart; and new devices for institution of extracorporeal membrane oxygenation. is approached by other guideline developers and asked to review and consider guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
101
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 98 publications
0
101
0
4
Order By: Relevance
“…Additionally, they also maintain coronary artery and endorgan perfusion. 19 They have been shown to be of potential benefit in select patients undergoing high-risk percutaneous coronary intervention, acute myocardial infarction, acute decompensated heart failure, and cardiogenic shock. [20][21][22][23] Because robust clinical evidence is lacking, the Society for Cardiovascular Angiography and Interventions/American College of Cardiology/Heart Failure Society of America/and Society of Thoracic Surgeons have provided a recent expert consensus statement in terms of patient populations that may derive benefit from these devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they also maintain coronary artery and endorgan perfusion. 19 They have been shown to be of potential benefit in select patients undergoing high-risk percutaneous coronary intervention, acute myocardial infarction, acute decompensated heart failure, and cardiogenic shock. [20][21][22][23] Because robust clinical evidence is lacking, the Society for Cardiovascular Angiography and Interventions/American College of Cardiology/Heart Failure Society of America/and Society of Thoracic Surgeons have provided a recent expert consensus statement in terms of patient populations that may derive benefit from these devices.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Because robust clinical evidence is lacking, the Society for Cardiovascular Angiography and Interventions/American College of Cardiology/Heart Failure Society of America/and Society of Thoracic Surgeons have provided a recent expert consensus statement in terms of patient populations that may derive benefit from these devices. 19 In a small single-center study of patients undergoing ablation for scar-related VT, we previously reported that pLVADs provided sufficient hemodynamic support to allow patients to be maintained in VT 2.5-fold longer, with fewer premature terminations required for hemodynamic instability, and allowed more patients to have termination of VT during ablation without any deleterious effects on end-organ perfusion. In a prospective evaluation of pLVADs, patients were maintained in VT for nearly 1 hour.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, MCS is an important therapeutic option for patients with advanced heart failure, including those with cardiogenic shock, and all AHFTC trainees should acquire competency in the use of these technologies. Trainees should understand the results of relevant clinical trials and registry data, maintain currency on contemporary guidelines for management of patients with mechanical support, [9][10][11] and keep abreast of emerging MCS technologies. It is essential that trainees learn to identify appropriate candidates for temporary hemodynamic support and durable ventricular assist devices.…”
Section: Mechanical Circulatory Supportmentioning
confidence: 99%
“…Use of percutaneously delivered, acute circulatory support devices for cardiogenic shock has grown exponentially due in large part to increasing global familiarity and clinical experience demonstrating hemodynamic efficacy of these devices. 1 Until recently, percutaneous support options for biventricular failure have been limited to venoarterial extracorporeal membrane oxygenation or biventricular centrifugal flow pumps. We recently reported the first use of biventricular axial flow catheters with the Impella 5.0 and RP (Abiomed Inc) systems, which required surgical vascular access for the 5.0 implant.…”
mentioning
confidence: 99%